Treatment-related changes in serum lipids and inflammation: clinical relevance remains unclear. Analyses from the Women's Interagency HIV Study - Parrinello, Christina M (2013)
Among 127 HIV-infected women, the magnitude of HDLc increases after HAART initiation predicted the magnitude of concurrent decreases in inflammation biomarkers. After HAART initiation, changes in LDLc and inflammation were unrelated. In the same population, predicted risk of coronary heart disease based upon levels of standard clinical risk factors was similar before and after HAART treatment. Thus, it remains unknown whether short-term treatment-related changes in standard risk factors may appreciably change risk of CVD.